The Factors Implementation of Green IT in Organization - Nur Amira Athira, Mohd Tahar; Awanis, Romli (2016)
The objectives of this research is to develop a checklist system for Green IT factors. This system aims to promote Green IT for organization to implement in their company and also to propose how to reduce the cost of energy consumption in the organization. Green IT is a set of practical measures designed to ensure that Information Technology is developed, delivered and used in a way that .is environmentally friendly, sustainable and energy efficient